Introducing new diagnostics into STI control programmes: the importance of programme science. Issue 2 (27th December 2012) - Peeling, Rosanna W; Mabey, David; Ballard, Ronald C
Abstract : Many innovative diagnostic technologies will become commercially available over the next 5–10 years. These tests can potentially transform the diagnosis of sexually transmitted infections but their introduction into control programmes can be hampered by health system constraints, and political, cultural, socioeconomic and behavioural factors. We used the introduction of syphilis rapid tests to illustrate the importance of programme science to address the gap between accruing evidence of acceptable test performance and the complexity of programme design, implementation and evaluation of test deployment to address public health needs and improve patient-important outcomes.